Educational Thought of K.H. Ahmad Shohibul Wafa Tajul 'Arifin and its Implementation in the Institution Suryalaya Islamic Boarding School - Wawan Wawan; Agus Salim Mansyur; Ahmad Tafsir; Aan Hasanah (Jurnal Impresi Indonesia, 2024)
KH Ahmad Shohibul Wafa Tajul 'Arifin's (Abah Anom) thoughts on Islamic education have important relevance in the revitalization of education in Indonesia, especially in the aspect of exemplary. This study aims to identify and analyze the implementation of Abah Anom's teachings in shaping student character at Suryalaya Islamic Boarding School and evaluate its impact on Islamic education as a whole. This research uses a descriptive method with an ethnographic model to understand the implementation of education at the Suryalaya Islamic Boarding School. Data were collected through observation and interviews with teachers and students. The implementation of Abah Anom's TQN teachings in Suryalaya succeeded in shaping the character of Muslims who have the quality of dhikr, thought, and charity. The educational approach that prioritizes akhlakul karimah and exemplary habituation by teachers has proven effective in creating a positive learning environment. The results show that education based on exemplary can overcome the decline in the values of formal education. Abah Anom's teachings emphasize the importance of spiritual and moral relationships in education, which can be a solution to achieving national goals in the context of Islamic education in Indonesia.